The influence of green marketing on sustainable consumption: a survey in Rio Grande do Norte - Severo, Eliana Andréa (2020)
The environmental problem impacts the environment, and is a key factor in the decision to purchase consumers. The objective of this study is to analyze the influence of green marketing on sustainable consumption to the perception of 820 consumers in Rio Grande do Norte (RN). The methodology used was a quantitative and descriptive research, through confirmatory factorial analysis and multiple linear regression. The results show that the green marketing has a moderate intensity and influences 43.7% sustainable consumption in the RN. These findings indicate that green marketing contributes to sustainable behaviors because it is evident that consumers perceive the environmental problem as well as influences the purchasing power of consumers, as well as making them future green consumers.